Dietary citrulline does not modify rat colon tumor response to chemotherapy, but failed to improve nutritional status. Issue 7 (July 2021) - Breuillard, C.; Moinard, C.; Goron, A.; Neveux, N.; De Reviers, A.; Mazurak, V.C.; Cynober, L.; Baracos, V.E.
Summary: During cancer therapy many patients experience significant malnutrition, leading to decreased tolerance to chemotherapy and decreased survival. Dietary citrulline supplementation improves nutritional status in situations such as short bowel syndrome and aging, and is of potential interest in oncology. However, a mandatory prerequisite is to test this amino acid for interaction with tumor growth and chemotherapy response. Dietary citrulline (Cit; 2%), or an isonitrogenous mix of non-essential amino acids (control), was given to Ward colon tumor-bearing rats the day before chemotherapy initiation. Chemotherapy included 2 cycles, one week apart, each consisting of one injection of CPT-11 (50 mg/kg) and of 5-fluorouracil (50 mg/kg) the day after. Body weight, food intake and tumor volume were measured daily. The day after the last injection, rats were killed, muscles ( EDL, gastrocnemius ), intestinal mucosa, tumor, spleen and liver were weighed. Muscle and intestinal mucosa protein content were measured. Phosphorylated 4E-BP1 was measured in muscle and tumor as a surrogate for biosynthetic activation. FRAPS (Ferric Reducing Ability of Plasma) and thiols in plasma, muscle and tumor were evaluated and plasma amino acids and haptoglobin were measured. Numerous parameters did not differ by diet overall: a) response of tumor mass to treatment, b) tumor antioxidants and phosphorylated 4E-BP1 levels, c) relative body weight and relative food intake, d) weight of EDL, gastrocnemius, intestinal mucosa, spleen and liver and e) plasma haptoglobin concentrations. Moreover, plasma citrulline concentration was not correlated to relative body weight, only cumulated food intake and plasma haptoglobin concentrations were correlated to relative body weight. Citrulline does not alter the tumor response to CPT-11/5FU based therapy but, has no effect on nutritional status, which could be due to the anorexia and the low amount of citrulline and protein ingested.